Development of a new emergency Medicine spinal Iimmobilization protocol for trauma patients and a test of applicability by German emergency care providers - Kreinest, Michael; Gliwitzky, Bernhard; Schüler, Svenja; Grützner, Paul Alfred; Münzberg, Matthias (Scandinavian journal of trauma, resuscitation and emergency medicine, 2016)
In order to match the challenges of quickly recognizing and treating any life-threatening injuries, the ABCDE principles were established for the assessment and treatment of trauma patients. The high priority of spine protection is emphasized by the fact that immobilization of the cervical spine is performed at the very first step in the ABCDE principles. Immobilization is typically performed to prevent or minimize secondary damage to the spinal cord if instability of the spinal column is suspected. Due to increasing reports about disadvantages of spinal immobilization, the indications for performing spinal immobilization must be refined.
Gesehen am 27.05.2016